RETRACTED: Increasing technological sovereignty in dump trucks production facing economic sanctions - Dubinkin D.M.; Golofastova N.N. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001